(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Researchers reported, in natural quartz probability of re-trapping of electrons by shallow TL traps gets reduced for Optically Stimulated Luminescence (OSL) at around 160 0C and usual shape of OSL decay curve is obtained. Under influence of critical physical condition followed by optical stimulation at room temperature in synthetic quartz material, identical OSL outcomes are observed. Below these critical physical conditions to the material neither usual shape of OSL decay curve is obtained nor does it give significant OSL signals. In current investigations, the consequence of different physical treatment on OSL decay curve of synthetic quartz material is studied. As an OSL outcome, the variations in shape of OSL decay curve as well as OSL strength over 0 to 100 seconds of stimulation time are discussed. Changes in OSL outcomes are responsible to strength of physical treatment to the sample and stimulation temperature followed by growth of favourable new centres. The unusual shape of OSL decay curve suggests the re trapping of optically unconfined electrons still occurred in traps rather than shallow TL traps corresponding to 110oC glow peak. The results are elaborated by resolving components of complex shapes of OSL decay curve and recorded TL glow curves before and after OSL for identical physical conditions to the sample.